Urban-rural differences in the impacts of multiple chronic disease on functional limitations and work productivity among Chinese adults - Yang Zhao; Li He; Chunlei Han; Brian Oldenburg; Grace Sum; Tilahun Nigatu Haregu; Xiaoyun Liu (Global Health Action)
Background Chronic disease multimorbidity has become a major challenge for health systems. While a lot of research has evaluated the direct economic burden of multimorbidity on health care utilization and cost, little attention has been given to the impacts on work productivity and functional limitations, as indirect indicators of disease burden. Objectives This study aims to examine the prevalence of multimorbidity among Chinese adults and its impact on functional disability and work productivity. It also investigates urban-rural differences in these relationships. Method This study utilized the data from the China Health and Retirement Longitudinal Study (CHARLS) in 2015, including 11,176 participants aged 45 years and older. Multivariable logistic regression models were used to estimate the effect of multimorbidity on functional disability (i.e. ADL: activities of daily life; IADL: instrumental activities of daily life), and work productivity loss due to health problems. Negative binomial regression models were used to assess the association of multimorbidity with sickness absences from agricultural work and employed non-agricultural work. Results 68.8% of total participants in CHARLS had multimorbidity in China in 2015. Rural residents with multimorbidity reported higher proportions of physical functions and days of sick leave than urban residents. Multimorbidity was positively associated with ADL limitation (odds ratio 1.924, 95% CI 1.656–2.236), IADL limitation (1.522, 1.326–1.748), limited work due to health problems (1.868, 1.601–2.178) and days of sick leave (for agricultural work, incidence rate ratio 1.676, 95% CI 1.390–2.020; for employed non-agricultural work, 2.418, 1.245–4.696). For the rural group, the impact of multimorbidity on functional limitations and work productivity loss (except for early retirement), was less than the urban group. Conclusions Multimorbidity poses significant challenges for functional health and work productivity These have significant negative economic consequences for individuals, the Chinese health system and the society.